Multidimensionality of religiosity and development of measurement instruments – an overview - Chaim, Władysław (Studia Psychologica: Theoria et praxis, 2012)
This article gives an overview of dimensional approach to religiousness; from the socioreligious core dimensions of religiousness of Stark & Glock (1968) to interdisciplinary model of religiosity od Huber with core dimensions, the centrality and content of religiosity (2003; 2008). The overview demonstrates the development of the succesive concepts of dimensional approach to religion as well as the constructed assesment techniques and their empirical applications. Then are the five core dimensions of religiousness (intelectual, ideological, experiencial, ritual, concequencial) synthetically organized by psychological contents. Especially the interdisciplinary model of religiosity of Huber is suitable for monitoring and interpreting religiousness of individuals, groups, of pantheistic or theistic patterns of religious expressions.